Reading No Country for Old Men and The Road: Trauma in Contemporary Literature and Cinema - Sadeghzadegan, Majid (2021)
Barely has literature failed to inspire the concept of trauma. Nor has trauma been a trivial cogitation for literature. This reciprocation, which is ingrained in the ineludible alliance between the two, has given rise to innumerable masterpieces throughout the history of literature from classic works of Homer to the modernist works of Woolf, Faulkner, and Hemingway. Nonetheless, trauma studies were not formulated in literature until two decades ago, which shapes an uncanny question mark never to be erased. Cormac McCarthy’s traumatic footprint in literature is as inerasable as the very same question mark, insofar as most, if not all, of his canon has been indelibly imbued with the notion of trauma. His characters seem to have a uniquely innovative bearing of traumatization, which is rarely found with that weight in other analogous works of literature. Chigurh, called the “prophet of destruction” by McCarthy himself in No Country for Old Men (2005), punches a hole into the forehead of his victims, leaving his vile mark metaphorically on the decaying civilization. Ballard in Child of God (1973), in what is termed as necrophilia, makes love to his victims, while judge Holden in Blood Meridian (1985) kills children, collects scalps, and never dies. This traumatic road eventually boils down to The Road (2006) in which everything comes to naught: an ashen apocalypse. Lending themselves to widespread critical acclaim, the novels No Country for Old Men and The Road did not fail to lend themselves to silver screen translations, which were indebted to the directorial efforts of the Coen brothers and John Hillcoat in 2007 and 2009, respectively. The narratives, textually or visually, are densely informed, if not formed, by the notion of trauma, which consolidates not only the bond between the two novels but also the traumatic trajectory from the novels to the films. It is thus through a thoroughgoing analysis of trauma and its footprints that a mastery of the inner workings, mysteries, and thematics of the aforementioned narratives will come to life, which is what the present dissertation aspires to achieve. Composed of three chapters, the foregoing dissertation sets out to initially establish the theoretical framework for trauma notions in chapter one whose application will shape the arguments of chapters two and three for the novels/films No Country for Old Men and The Road, respectively.